Comparison of low‐ and ultralow‐dose computed tomography protocols for quantitative lung and airway assessment. Issue 9 (2nd August 2017) - Hammond, Emily; Sloan, Chelsea; Newell, John D.; Sieren, Jered P.; Saylor, Melissa; Vidal, Craig; Hogue, Shayna; De Stefano, Frank; Sieren, Alexa; Hoffman, Eric A.; Sieren, Jessica C.
Abstract : Purpose: Quantitative computed tomography (CT) measures are increasingly being developed and used to characterize lung disease. With recent advances in CT technologies, we sought to evaluate the quantitative accuracy of lung imaging at low‐ and ultralow‐radiation doses with the use of iterative reconstruction (IR), tube current modulation (TCM), and spectral shaping. Methods: We investigated the effect of five independent CT protocols reconstructed with IR on quantitative airway measures and global lung measures using an in vivo large animal model as a human subject surrogate. A control protocol was chosen (NIH‐SPIROMICS + TCM) and five independent protocols investigating TCM, low‐ and ultralow‐radiation dose, and spectral shaping. For all scans, quantitative global parenchymal measurements (mean, median and standard deviation of the parenchymal HU, along with measures of emphysema) and global airway measurements (number of segmented airways and pi10) were generated. In addition, selected individual airway measurements (minor and major inner diameter, wall thickness, inner and outer area, inner and outer perimeter, wall area fraction, and inner equivalent circle diameter) were evaluated. Comparisons were made between control and target protocols using difference and repeatability measures. Results: Estimated CT volume dose index (CTDIvol) across all protocols ranged from 7.32 mGy to 0.32 mGy. Low‐ and ultralow‐dose protocols required more manual editing and resolved fewer airway branches; yet, comparable pi10 whole lung measures were observed across all protocols. Similar trends in acquired parenchymal and airway measurements were observed across all protocols, with increased measurement differences using the ultralow‐dose protocols. However, for small airways (1.9 ± 0.2 mm) and medium airways (5.7 ± 0.4 mm), the measurement differences across all protocols were comparable to the control protocol repeatability across breath holds. Diameters, wall thickness, wall area fraction, and equivalent diameter had smaller measurement differences than area and perimeter measurements. Conclusions: In conclusion, the use of IR with low‐ and ultralow‐dose CT protocols with CT volume dose indices down to 0.32 mGy maintains selected quantitative parenchymal and airway measurements relevant to pulmonary disease characterization.